A robust Pax7EGFP mouse that enables the visualization of dynamic behaviors of muscle stem cells. - Tichy, Elisia D.; Sidibe, David K.; Greer, Christopher D.; Oyster, Nicholas M.; Rompolas, Panteleimon.; Rosenthal, Nadia A.; Blau, Helen M.; Mourkioti, Foteini. (2018)
Background: Pax7 is a transcription factor involved in the specification and maintenance of muscle stem cells (MuSCs). Upon injury, MuSCs leave their quiescent state, downregulate Pax7 and differentiate, contributing to skeletal muscle regeneration. In the majority of regeneration studies, MuSCs are isolated by fluorescence-activated sorting (FACS), based on cell surface markers. It is known that MuSCs are a heterogeneous population and only a small percentage of isolated cells are true stem cells that are able to self-renew. A strong Pax7 reporter line would be valuable to study the in vivo behavior of Pax7-expressing stem cells.; Keywords: Skeletal muscle, Pax7, EGFP, Muscle stem cell, Satellite cell, Muscle development, Muscle regeneration, Fluorescence-activated cell sorting.; Springer Open.